Angka Kejadian Stunting Dan Faktor-Faktor Yang Memengaruhinya Pada Balita Usia 2–5 Tahun Di Wilayah Kerja Puskesmas Kota, Kecamatan Enrekang, Kabupaten Enrekang Pada Tahun 2020 - Faisal, Abdul Azis; Sari, Jelita Inayah; Darmawansyih, Darmawansyih; Tanri, Hamidah; S.Puyu , Dasrul (Green Publisher Indonesia, 2025)
Stunting is a growth disorder in children, characterized by height that is below the expected standard for their age, leading to delays in physical and cognitive development. This study aims to determine the prevalence of stunting in children aged 2-5 years at the working area of Puskesmas Kota, Enrekang Subdistrict, Enrekang District, in 2020, and analyze the factors influencing stunting occurrence. The study used an observational method with a cross-sectional approach, involving 87 children as samples. Data were collected through interviews, questionnaires, and anthropometric measurements. The results revealed that 63.2% of the children were stunted, and the factors influencing stunting included parenting patterns, parental education level, parental financial status, and parental height. Statistical tests showed a significant relationship between these factors and the occurrence of stunting in children (p<0.05). The conclusion of this study is that high prevalence of stunting is influenced by parenting, education, financial status, and parental height in Puskesmas Kota, Enrekang